Knowledge and use of hormone replacement among climacteric women of middle class in Lima - Távara, Luis (2015)
OBJECTIVE: To determine menopausal women's knowledge, use and reasons for nott using HRT MATERIAL AND METHODS: Epidemiologic descriptive cross-sectional study through a semiestructured questionnaire applied to 500 middle-class women 45 through 65-year-old, with high school or superior education. RESULTS: Women were either house wives, office workers, managers or professionals; 68,4% had sometime talked about climacteric and menopause with their doctor, 11,6% said they knew much about HRT 76,5% knew only little and 12,7% did not know about HRT Information was mainly given by gynecologists, and by social media in 17,8%. Tablets and injectables were presentations most frequently known. In women that knew about HRT 58% said it improved depression and mood, 52,8% bot-flushes, 22% vaginal diyness, 51% osteoporosis and 25% myocardial infarction. Only 19,6% currently used HRT 26,8% said thay used it in the past and 53,6% had never used it. Parenteral estrogens were used by 20,8% and tablets by 16,4%; 11,4% started HRT without medical indication and most women on HRT said they were satisfied, although over half did not know bow long to use it. Among non-users of HRT 55% said they could stay without it. CONCLUSION: Women must be well informed about HRT through better doctor-patient communication and public education al programs in order to take correct decisions.